Clinical characteristics and positive airway pressure adherence among elderly European sleep apnoea patients from the ESADA cohort - Aino Lammintausta; Ulla Anttalainen; Özen K. Basoglu; Maria R. Bonsignore; Haralampos Gouveris; Ludger Grote; Jan Hedner; Ondrej Ludka; Stefan Mihaicuta; Athanasia Pataka; Georgia Trakada; Mafalda van Zeller; et al. (ERJ Open Research, 2023)
Background The prevalence of obstructive sleep apnoea (OSA) is growing as the population is ageing. However, data on the clinical characteristics of elderly patients with OSA and their adherence to positive airway pressure (PAP) treatment are scarce. Methods Data from 23 418 30–79-year-old OSA patients prospectively collected into the ESADA database during 2007–2019 were analysed. Information on PAP use (h·day−1) in association with a first follow-up visit was available for 6547 patients. The data was analysed according to 10-year age groups. Results The oldest age group was less obese, less sleepy and had a lower apnoea–hypopnoea index (AHI) compared with middle-aged patients. The insomnia phenotype of OSA was more prevalent in the oldest age group than in the middle-aged group (36%, 95% CI 34–38 versus 26%, 95% CI 24–27, p<0.001). The 70–79-year-old group adhered to PAP therapy equally well as the younger age groups with a mean PAP use of 5.59 h·day−1 (95% CI 5.44–5.75). PAP adherence did not differ between clinical phenotypes based on subjective daytime sleepiness and sleep complaints suggestive of insomnia in the oldest age group. A higher score on the Clinical Global Impression Severity (CGI-S) scale predicted poorer PAP adherence. Conclusion The elderly patient group was less obese, less sleepy, had more insomnia symptoms and less severe OSA, but were rated to be more ill compared with the middle-aged patients. Elderly patients with OSA adhered to PAP therapy equally well as middle-aged patients. Low global functioning (measured by CGI-S) in the elderly patient predicted poorer PAP adherence.